Evaluación de la gestión territorial del predio estatal denominado zona de conservación y recuperación de ecosistemas (ZoCRE) Juninquillo – Yanayacu - Santamaría Vilchez, Luis Genner (2014)
The present thesis entitled: Evaluation of the Territorial Management of the S tate Land Named Conservation and Recovery of Ecosystems Zone (ZoCRE) Juninguillo - Yanayacu, San Martín - Peru, specific aims: "diagnose the current situation and raise planning strategies" as well as "propose a design ofterritorial management plan" ofthe venue before mentioned state. The diagnosis of the current situation of the farm state, it was determined that is located in the of Moyobamba and Pinto Recodo districts; and has an extension of 21023.66 hectares with a perimeter of 127.46 km. In addition it counts with: six ecological economic zones being that of major extension the protection zones of head-board of basin with an area of 12869.65 it has. That represents 61.22 % of the total area; five classes of current land use within which we find primary forest with an area of 13,222.82 has been representing the 62.90 % of the total area, two areas of life and a transitional training, two ecosystems (wet forest low mountain, humid forest of high mountains), within the first ecosystem we found wildlife, such as: majas, sajino, añuje, Kettle of mount; within the flora to cedro, marona, oje. Within the ecosystem services that gives us the venue we state: hydrological provision, regulation of the erosion and maintenance of soil fertility, support of species habitats and scenic beauty and landscape. In addition, it has ten primary actors, six secondary actors and thirteen actors allies. For planning strategies, this is based on principies such as sustainability, environmental responsibility, among others. Within the strategies presents strategies of territorial management, a forward-looking vision, mechanisms for the sustainable use of natural resources as well as state zoning of the property. The design of the Plan presented in this document directs the management of the farm state. Still this venue a space state of preservation, it is necessary to make changes in the use of space and resources, from the traditional form of use, to a new principie that where the prime is the conservation of the area.Basically, the plan env1sages strategic ways to achieve these changes, with the participation of the users of the area and the people responsible for it, in this case, the San Martin Regional Government through the Regional Environmental Authority, and is oriented to achieve and maintain benefits, direct and indirect for local populations. The plan presents the departure situation on a diagnostic that includes both the physical and biological environment, such as the social, cultural and political. Then develops participatory vision with the changes that you want to achieve and presents the strategies to achieve these changes. As a result this study is the fiuit of the participative work of the inhabitants of different population centers that are found in the interior and state adjacent to the venue, the technical team that guided me in this research, in collaboration with the my adviser and coasesor. Key words: Territorial Management, ecological economic zones. JR.